Medical economic burden of the ageing population: a multistage sampling analysis of 3 532 517 cases. (October 2016) - Yang, Yunbin; Zheng, Ang; Li, Mingyang; Duan, Wenjuan; Mu, Xin; Wang, Xin
Abstract: Background: Population ageing and the economic burden of aged disease have become topical issues in global health. The situation seems worse in China, which has 140 million people older than 65 years. We analysed the medical economic burden in Liaoning Province, China, and laid stress on the population aged 65 years and older. Methods: We used a multistage random sampling method for selecting 252 medical institutions from four cities, Panjin, Tieling, Dalian, and Liaoyang, in Liaoning Province. We established a standardised database for medical expense between Jan 1, 2014, and Dec 31, 2014, using a new internationally recognised accounting system, System of Health Accounts 2011 (SHA2011). We classified expenses by disease based on ICD-10 and compared per-capita medical expense between age groups. We used SPSS22·0 and STATA12·0 to analyse the medical economic burden. The study was approved by Medical Ethics Committee of China Medical University and all patients' information was collected with written informed consents. Findings: We obtained medical expense data for the year of 2014 from 252 institutions, including data for 3 532 517 patients. Circulation system disease (32·10%, 95% CI 32·05–32·15) and digestive system disease (11·56%, 11·54–11·58) constituted nearly half of the medical expenses. Among the population aged older than 65 years, cardiovascular disease (31·39%, 31·35–31·43), respiratory diseases (27·83%, 27·79–27·8), and digestive diseases (23·56%, 23·52–23·60) were the major burden. The aged population constituted 11·52% (4·88 million) of total Liaoning population, but spent 29·71% (95% CI 29·69–29·7) of the medical expenses. The per capita medical expense of the aged population (US$520·86, CNY 3 199 52) was nearly three times that of those aged 14–65 years ($163·45, CNY 1 004·04) and four times that of those aged 0–14 years ($139·02, CNY 853·96). Interpretation: Cardiovascular diseases bring the heaviest medical economic burden, but the rise in respiratory and digestive diseases among the aged population deserves attention. The aged diseases cost a large proportion of medical expenses. This study raises advanced counting models and control strategies on medical expenses. More researches in other provinces are ongoing and will be discussed later. Funding: National Natural Science Foundation of China (71673299) and the Seventeenth Subject by China Health Economics Association (CHEA1617070102).